Cutting tool condition monitoring system for high-speed turning operations. (2nd August 2010) - Chelladurai, H.; Jain, V.K.; Vyas, N.S.
In this paper, an attempt has been made to create artificial flank wear using Electrical Discharge Machining (EDM) process. Experiments have been conducted to evaluate vibration and strain responses of cutting tool for various cutting speeds, depths of cut and feed rates. To increase the confidence limit, experimental work has been carried out for full factorial design (135 experiments). Vibration and strain data from the cutting process are recorded using two accelerometers and a strain gauge bridge. Power spectral analysis is carried out and a statistical model is developed for empirical prediction of the condition of the cutting tool. The amplitude of vibration and strain were measured at the tool's natural frequency. Experimental results are analysed with respect to depth of cut, feed rate and cutting speed.